Possibility of intrinsic muscle contractile properties as an index of maximal muscle strength and muscle fatigue - Ohta, Y.; Takahashi, K.; Matsubayashi, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
This study aimed to investigate whether the measurement of intrinsic muscle contractile properties is an index of maximal muscle strength and muscle contractile fatigue. Methods: Seven subjects performed a fatiguing exercise involving 3 bouts of 120-s repeated right-ankle dorsiflexion at a frequency of 1 Hz with a 5-min rest period between bouts. Thirty percent of maximum voluntary dorsiflexion torque (MVC) measured at an ankle angle of 90° was used as the resistance load in the fatigue exercise. Intrinsic muscle contractile properties were defined as evoked peak torque (single stimulus, two-pulse trains, and three-pulse trains), post-activation potentiation (PAP), and ability of torque summation. The ability of torque summation was estimated by torque contribution of second stimuli of two-pulse trains (C2) and third contribution of three pulse trains (C3). The contribution of the response to the Nth stimulation was determined by subtracting the response to the N-1 stimulation from that to the N stimulation. Non-PAP-evoked torques, PAP-evoked torques, and MVC torques of dorsiflexion at isometric contractions were measured at an ankle angle of 90° in each rest period. The electrical stimulation was delivered from the common peroneal nerve near the fibular head. The responses to two-pulse trains and to three-pulse trains, which were delivered with a constant inter-pulse interval of 10 ms (100 Hz), were recorded. Results and discussion: Regardless of with or without PAP, the peak torque evoked by a single stimulus, two-pulse trains, and three-pulse trains decreased with the increase in fatigue. Although C2 and C3 without PAP decreased with the increase in fatigue, the pattern of changes in C2 and C3 with PAP differed from that in other parameters. The percent fall was greater in the evoked torque parameters than in the MVC torque. These results suggest that the measurement of intrinsic muscle contractile properties overestimates the muscle fatigue during MVC of dorsiflexion at isometric contraction. Moreover, the present study found that, with or without fatigue, the absolute value of evoked peak torque showed a significant positive correlation with MVC torque. In addition, significant relationships were found between MVC torque and magnitude of PAP and between MVC torque and magnitude of ability of torque summation by a second stimulus. Thus, the measurement of intrinsic muscle contractile properties can be used as an index of maximal muscle strength with or without fatigue.